Flow of materials in a market system: food security and environmental sustainability perspective - Ngusale, George K.; Oloko, Michael O. (Research Gate, 2018)
Worldwide, there is a challenge of feeding growing population calling for discussions on flow of food materials in a market system. In Kenya, this discussion has been lacking that could aid in identification of opportunities for ensuring food security and environmental sustainability. This paper considered Kibuye market as a convergent area of food materials into Kisumu city. A survey was administered to market traders in Kibuye to ascertain products traded in market; their age and sex; source of products; quantity and types of wastes generated, among others. Results revealed majority of traders are women; highest level is primary education; most products are sourced outside Kisumu; most waste products are not sorted and recycled on disposal. This paper concludes that food security and environmental sustainability can be achieved through proper design of market sections; adopting preservation technologies; sensitization and establishment of technology testing, demonstration and training sites.
Keywords: market systems; food security; food wastage; environmental sustainability; Kisumu; Kibuye.